Penerapan Metode Time-Driven Activity-Based Costing untuk Menetapkan Harga Pokok Penjualan Full Container Load pada PT. Sinar Garuda Pasifik di Surabaya - Dewi Kumala Sari; Tjandra Wasesa; Heri Toni Hendro P; Wiratna Wiratna; Diana Zuhroh (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study applies the Time-Driven Activity-Based Costing method to determine the cost of goods sold for Full Container Load shipping services at a freight forwarder company in Surabaya and examines its impact on the current determination of the cost of goods sold. Some previous research has focused on employee efficiency with precise measurements, thereby overlooking the strengths of the Time-Driven Activity-Based Costing method, which are simplicity and reliance on estimation. This study found that indirect costs contribute insignificantly to the determination of the cost of goods sold. Nevertheless, this method is capable of accurately determining the cost of goods in transactions with low-profit margins, which is characteristic of companies like freight forwarders, where the percentage of direct costs in the cost of goods sold is high.